STUDI PERBANDINGAN ARSITEKTUR TRADISIONAL ANGKOLA DENGAN ARSITEKTUR TRADISIONAL BATAK TOBA DITINJAU DARI STRUKTUR BANGUNAN - Giawa, Wengky Billy Putra; Pakpahan, Raimundus; Yulianto, Yulianto (ALUR :Jurnal Arsitektur, 2019)
The Batak are the majority in North Sumatra. The Batak tribe even has another sub-tribe, namely Toba  Batak, Karo Batak, Simalungun Batak, Mandailing Batak and Angkola Batak. Every Batak tribe has its own  distinctive culture and identity. Batak tribes have traditional buildings which are traditional Batak  architectural identities. The diversity of the Batak tribe caused the phenomenon of visual aspect equality in  traditional buildings because of the effects of secession and cultural integration. The Toba Batak  architecture has the concept of a stilt house and pointed gable construction in both directions and a peg and pen structure system is evidence of similarities with Angkola Batak architecture. Angkola Bataks are part of the Batak tribe. Angkola Batak is a tribe in the area of South Tapanuli. The Toba Batak is the center of the Batak culture. The Toba Batak has one of the traditional Sopo buildings, namely Sopo. Sopo functions as a barn, but also an art venue and meeting place. Angkola Batak has one traditional building that represents the traditional architecture of the Angkola Batak namely Sopo Godang. Serves as a meeting place for the king and the people. It is a place where tradition is based on Dalihan Na Tolu which produces consensus and mutual agreement (The King and People). Sopo Godang is a part of traditional Batak architecture that needs to be preserved. The benefit of this study is to collect data on traditional Angkola Batak architecture and data on structures that are characteristic of the Angkola Batak